ANALYSIS OF LEARNING READINESS IN IMPLEMENTATION OF SOCIO-SCIENTIFIC ISSUES BASED LEARNING - Ani Anjarwati (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2019)
The research objective is to obtain a picture of the readiness of learners in the implementation of learning based on socio-scientific issues (SSI). This student readiness description is reviewed from the variable of thinking skills, especially science process skills (KPS). If the student KPS is low, then the learner is actually not ready to be involved or participate in SSI-based learning. The research targets were junior high school students, high school students, and students of one of the PGSD study programs in FKIP of a PTS (Private Higher Education). KPS data for these three groups of learners was obtained using documentation and post facto methods. KPS data for junior high school students is taken from the results of Astuti's research (2018) and Jannah (2016). KPS data for high school students is taken from the results of the National Examination (UN). This data group collector uses the documentation method and data was analyzed descriptively. The KPS PGIP FKIP student data in a PTS is the result of an assessment using KPS questions that Monica has developed (2005). Student KPS data were analyzed descriptively. The results of KPS data analysis for junior high school students concluded that KPS for students from two state junior high schools in Surabaya was still relatively low. Nationally, KPS of SMA / MA students tends to be low. The national average percentage of students answering correctly the UN questions containing the KPS component in the last three years (2016-2018) is 46.97; 39.09; and 51.08% respectively for experimental design, data interpretation, and identification and control of variables. These percentages have not yet reached the classical completeness rate of 80%, so it is concluded that the KPS of high school students is relatively low. The same trend occurs at the level of the city of Surabaya as well as the province of East Java. The target KPS of PGSD students was also low. Mean KPS score of students on indicators identifying and controlling variables, stating hypotheses, making operational definitions of variables, interpreting data, and designing experiments in succession 73,14; 47.33; 43.33; 64; and 62. The average KPS score is still low, not yet achieving the lowest good score (70). The results of the study: (1) students' science process skills (KPS) in junior high, high school, and a PTS PGSD study program are classified as low and (2) not all learners are ready to be involved in the implementation of socio-scientific issues (SSI) based learning in terms of aspects of learner experiences specifically the ownership of science process skills